THE ROLE of ORGANIZATIONAL AMBIDEXTERITY TO INCREASE INNOVATION SPEED AND MARKETING PERFORMANCE of SMEs - Ken Sudarti; Nurhidayati Nurhidayati; Ardian Adhiatma (STIE Pelita Nusantara Semarang, 2019)
This study aims to investigate and test the role of organizational ambition in improving innovation speed and marketing performance in MSMEs in the creative industries, especially handicraft in Semarang, Central Java. A sample of 173 SMEs were taken using convenience sampling techniques. Using regression analysis techniques, the study concluded that innovation speed is more influenced by exploitation than exploration. Organizational ambidexterity is not able to increase innovation speed and marketing performance and innovation speed is only influenced by exploitation. This result is thought to be strongly influenced by the character of MSMEs who are less familiar with technology as supporting exploitation activities. Exploitation capabilities are more prominent because modifying products by changing shapes, colors and sizes is easier and lower risk compared to creating products that are completely new with the use of the latest technology.